Shari’ah principles of preventing financial crisis in Islamic finance - Adam Sa'ad, Auwal; Hj Ibrahim, Badruddin; Abdul Kadir Malim, Nurhafiza (2018)
The study looks into the potential Shari’ah principles and ethics as measures to preventing financial crisis in Islamic finance. Library research method adopted to gather information related to the Islamic principles preventing financial crisis in Islamic finance. Islamic ethics and Shari’ah principles are vital to preventing financial crisis in Islamic finance. Shari’ah promotes trustworthiness, God-fearing and general ethics while doing business in an Islamic marketplace. The system encourages market observation and surveillance to ensure a strict adherence to the Islamic ethics and trustworthiness. Islamic financial system prohibits interest taking, gambling, sale of debt for debt. This has prevented the Islamic financial market atmosphere from deceptive activities that actually cause mistrust and panic which lead to a financial crisis. Islamic business ethics and the Shari’ah principles are the twin factors which can sustain the investor confidence within the Islamic financial institutions.